Utilización del transporte intermodal para mejorar la competitividad y el desarrollo: corredor Bogotá-Belencito (2017)
The department of Boyacá is known for the diversity of its territory thanks to its geographical position, which has allowed it to have an agricultural vocation, in which family-type production predominates. The region has comparative and competitive advantages, which at the same time, are limited by various problems, which is why an inventory of agricultural potentialities was made in order to establish policy and transport proposals, that lead the farming sector to increase its productivity and competitiveness, without ignoring the heterogeneity and diversity that characterizes this department.